Initial Returns Determinants with the Underwriter’s Reputation as a Moderating Factor - Dewi Cahyani Pangestuti (Universitas Pendidikan Indonesia, 2022)
Main purpose- The main purpose of this study is to find out the factors that affect the initial return. Accounting information and non-accounting information are components that determine the initial return that needs to be considered.Method - The population used is all companies that conducted initial public offerings (IPOs) on the Indonesia Stock Exchange (IDX) in the 2016-2020 period. In this study, the sampling technique used was non-probability sampling with a saturated sample technique of 135 companies. This study used multiple linear regression analysis to test its hypothesis.Main Findings-The results of the hypothesis testing concluded that the return on assets has a positive and significant effect on the initial return. The underwriter's reputation was able to moderate the relationship between return on assets and initial returns. The debt-to-equity ratio has a significant negative effect on the initial return. The underwriter's reputation was able to moderate the relationship between the debt-to-equity ratio and initial return. The current ratio positively and not significantly affect the initial return on investment. The underwriter's reputation was able to moderate the relationship between the current ratio and the initial return. The company's size positively and significantly affects the initial return. The underwriter's reputation was able to moderate the relationship of company size to initial return. Earnings per share have a negative and significant effect on initial returns. The underwriter's reputation cannot be moderated on earnings per share versus initial return. The price-earnings ratio has a positive but not significant effect on the initial return.Theory and Practical Implications - The findings of this study have implications for initial public offerings (IPOs) in the primary market, as well as parties who will conduct further research on factors that affect initial returns, such as issuers who will go public. These investors will make decisions about investing in companies with high underpricing rates. The results of this study are expected to contribute to the company or issuer, and also to investors who will invest that the underwriter's reputation can moderate the influence of ROA, DER, SIZE, and EPS on the initial return.Novelty- The novelty in this study is to use the underwriter reputation variable as a moderation variable that will strengthen the influence of the ROA, DER, CR, Ln Size, EPS, and PER variables on the initial return, whereas previous studies did not use it as a moderation variable.